Postnatal Prebiotic Fiber Intake in Offspring Exposed to Gestational Protein Restriction Has Sex-Specific Effects on Insulin Resistance and Intestinal Permeability in Rats. Issue 10 (30th July 2014) - Hallam, Megan C.; Reimer, Raylene A.
Abstract: Maternal protein restriction (PR) during pregnancy is known to have numerous adverse effects on offspring, including increased adiposity and impaired glucose tolerance later in life. A few studies have shown that this adverse programming can be reversed by dietary or hormonal therapies early in postnatal life. The objective of this study was to determine if a weaning diet high in prebiotic fiber could mitigate some of the negative effects of maternal PR, such as increased adiposity and impaired glucose tolerance. Wistar rats were fed a low- (8%) or normal- (20%) protein diet during pregnancy. Male and female pups were weaned onto control (C; 5% fiber, 20% protein) or high (prebiotic) fiber (HF; 21% wt:wt, 1:1 ratio oligofructose and inulin at 4–10 wk; 10% wt:wt, 1:1 ratio oligofructose and inulin at 10–24 wk; 17.3% protein) diets. At 24 wk of age, glucose tolerance, body composition, satiety hormones, gut microbiota, and markers of intestinal permeability were measured in the offspring. Maternal PR reduced offspring birth weight by 5% and lean mass by 9% compared with the C offspring ( P < 0.007). HF-fed offspring had lower body weights and percentage body fat (∼23% in males, ∼19% in females) at 24 wk than did C offspring ( P < 0.02). Compared with C pups, pups fed the HF diet had greater cecal Bifidobacterium spp. (>5-fold) and plasma concentrations of the gut trophic hormone glucagon-like peptide 2 (GLP-2) ( P < 0.05). In male PR offspring fed the HF diet, insulin resistance measured by the homeostasis model assessment of insulin resistance was reduced by 81% compared with those fed the C diet ( P = 0.02). In female PR offspring fed the HF diet, plasma endotoxin was greater and colonic tight junction protein 1 ( Tjp1 ) expression was lower than in those fed the C diet. A high prebiotic fiber weaning diet mitigated increased adiposity and insulin resistance associated with maternal PR, which could improve health and decrease risk of chronic disease in offspring born to malnourished dams. However, the functional importance of sex-specific changes in markers of intestinal barrier function warrants further investigation.